Readings in Islamic banking - Hoque, Ataul (Dhaka : Islamic Foundation Bangladesh, 1987)
Selected papers from a seminar sponsored by the Bangladesh Institute of Bank Management, Dhaka, 1981.
Includes bibliographies.
Keywords: Banks and banking -- Islamic countries -- Congresses; Banks and banking -- Religious aspects -- Islam -- Congresses; Islam -- Economic aspects -- Congresses; Economics -- Religious aspects -- Islam -- Congresses